Cement, Graves, and Pillars in Land Disputes in Northern Uganda. (8th November 2017) - Meinert, Lotte; Willerslev, Rane; Seebach, Sophie Hooge
Abstract: Cement pillars and graves play significant roles as land markers in disputes over land in postconflict northern Uganda. Contemporary land cases from Acholi and Ikland display different histories of land use and conflict. In Acholi, cemented graves constitute concrete indices of belonging in wrangles. In Ikland, national nature authorities have brought cement pillars into the landscape. We explore how cemented graves and cement pillars are used for land claims in societies affected by conflict and displacement and how articulations of belonging are created, with the specific materiality of cement signaling modernity, permanence, and inflexibility. Résumé: Tombes et piliers de ciment jouent un rôle important en tant que marqueurs de terrain dans les conflits fonciers après le conflit dans le nord de l'Ouganda. Dans la région Acholi de l'après-guerre, les tombes en ciment sont des preuves de propriété, la réinhumation des parents dans les terres contestées peut être une stratégie dans les conflits fonciers. Dans les frontières terrestres de Ikland, le placement des morts vient maintenant marquer les différends sur le territoire entre les autorités nationales de protection de la nature et les habitants locaux. L'article montre comment les tombes sont utilisées à la fois comme ancêtres spirituels d'appartenance et preuves de la propriété foncière dans les tentatives de créer permanence.